ANALISIS MUTU PELAYANAN DI PUSKESMAS GALANG BERDASARKAN INDIKATOR NASIONAL MUTU PELAYANAN KESEHATAN - prem punjabi (Jurnal Inovasi Kesehatan Masyarakat, 2023)
Puskesmas is the main door in implementing basic health efforts including planning, implementing, evaluating, recording, reporting, and as outlined in a system. Quality of service is one of the efforts to fulfill the desires of customers and the accuracy of delivery to match customer expectations. This study aims to analyze the Service Quality of the Puskesmas Galang based on the National Indicators of Health Service Quality by using a qualitative descriptive study conducted from November 2022 to March 2023. This study used the Exponential Non-Discriminative Snowball Sampling technique with 12 informants consisting of 2 representatives from the Community Health Efforts (UKM) Section for Individual Health Nursing (UKP), 2 representatives from the Public Health Efforts (UKM) Development section, 2 representatives from the Individual Health Efforts (UKP) Health Center Service Network section, 2 representatives from the Puskesmas Facilities Network (Puskesmas Auxiliary, Poskesdes and Village Maternity Polyclinic), 4 representatives from the community who came to the puskesmas to get health services at the Puskesmas Galang. The results of the analysis concluded that it is necessary to procure educational media for hand hygiene and the use of PPE in strategic areas and facilities for more adequate sputum examination so that sputum examination can be carried out at the puskesmas. It is suggested to the Puskesmas to carry out regular training and routine monitoring related to hand hygiene and the use of personal protective equipment, periodic training on the use of SITB and Cohort applications for TB officers and ANC services for pregnant women and the Health Service needs to provide medical technicians for routine monitoring and repair if found damaged Puskesmas advice and infrastructure.